Tangential Loewner hulls - Lind, Joan (Annales Fennici Mathematici, 2021)
Through the Loewner equation, real-valued driving functions generate sets called Loewner hulls. We analyze driving functions that approach 0 at least as fast as \(a (T-t)^r\) as \(t → T\), where \(r (0, 1/2)\), and show that the corresponding Loewner hulls have tangential behavior at time \(T\). We also prove a result about trace existence and apply it to show that the Loewner hulls driven by \(a(T-t)^r\) for \(r (0,1/2)\) have a tangential trace curve.